Aphelenchoides spp. (Nematoda: Aphelenchida) and Panagrolaimus leperisini (Nematoda: Rhabditida) found associated with grass seeds in the Telperion Nature Reserve, South Africa - Girgan, Chantelle; Swart, Antoinette; Marais, Mariette; Fourie, Hendrika (Zootaxa, 2018)
As part of the South African Plant-Parasitic Nematode Survey (SAPPNS), an extensive nematode diversity survey was conducted in the Telperion Nature Reserve, Mpumalanga, South Africa. During this survey, samples of grass seeds were collected. Some of these seeds yielded specimens of the genera Aphelenchoides, Aphelenchus and Panagrolaimus. Identified species include Aphelenchoides africanus, A. besseyi, A. lichenicola, A. rutgersi, A. spicomucronatus and Panagrolaimus leperisini. Four of these species are new records for South Africa and the South African populations of these species are described in this paper.